IDEA's Double Bind: A Synthesis of Disproportionality Policy Interpretations. (July 2019) - Sullivan, Amanda L.; Osher, Daniel
Disproportionality research has been subject to multiple reviews, but there has been less critical examination of the policy dimension of this enduring educational problem. Given the relevance of federal policies, and interpretations thereof, to educators' and scholars' conceptualization of disproportionality and schools' resultant policies and practices, we provide a brief overview of disproportionality scholarship before focusing on its policy dimensions. We describe the role of federal policy and resultant interpretations to how disproportionality is addressed and our approach to identifying and synthesizing these interpretations. We then analyze the themes apparent in these interpretations: requirements for states' numerical analysis of "significant disproportionality, " parameters for school systems' allocation of resources for early intervening services when significant disproportionality is found, and schools' obligations for nondiscriminatory application of policies and procedures. Finally, we distill implications for school policies, practices, and procedures. We close with discussion of implications for how disproportionality is conceptualized and studied.